Effects of castration, dehorning, frame size, and gut fill on the long-term performance of feeder calves - Brazle, F.K.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In two experiments, calves purchased as steers gained substantially faster than calves purchased as bulls and then castrated, during both the starting period and the subsequent growing period. Large-framed calves gained .22 lb per day faster, and small-framed calves .21 lb per day slower, than medium-framed calves. Cattle appearing gaunt at the start of the trial gained 1.33 lb per day less than those with average gut fill.
Keywords: Beef; Castration; Dehorning; Frame size; Gut fill; Calves